Patenting strategies in the German mechanical engineering industry and their relationship to company performance - Ernst, H. (Technovation)
Fifty German mechanical engineering firms were studied with regard to their patenting behaviour. Four different patenting strategies were identified and the relationship between such strategies and company performances was evaluated.